Pengaruh Pembelajaran Online Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Matematika di Sekolah Dasar - Khurin In Ratnasari (JIEES : Journal of Islamic Education at Elementary School, 2022)
Learning outcomes are a measure of the extent to which students understand the learning material that has been taught by the teacher. Broadly speaking, several factors cause a decline in student learning outcomes in mathematics subjects at the time of online learning today, including several online media recommended by the government. However, schools take two online learning media recommended by the government, namely Zoom and Google Form. This is what attracts researchers who want to examine whether online learning affects student learning outcomes. The research method used uses quantitative research methods, data collection techniques using questionnaires, observations, and interviews and the results of the study show that there is an effect of online learning on the learning outcomes of mathematics subjects. The collaboration of parents and teachers is very much needed in online learning because the collaboration of parents and teachers can produce maximum learning outcomes even though there are some obstacles to learning such as weak signals, there are parents who do not understand the application on smartphones.